Use of organic waste and bokashi-type fermented compost in the development of cauliflower seedlings - Pinto, Geazí Penha; Ferreira, Regina Lúcia Felix; Araújo Neto, Sebastião Elviro de; Souza, Luís Gustavo de Souza e; Uchôa, Thays Lemos; Machado, Lucas (Comunicata Scientiae, 2023)
The economic assessment of the agricultural activity is essential to determine its viability. In this scenario, this study aimed to assess the economic profitability of organic carrot cultivation under different weed control and sowing methods. The experiment was conducted in Rio Branco, AC, from June to September 2018, and was followed a randomized block design set up in 4 x 3 split-plots corresponding to four control methods: dead plant mulching, plastic mulching, solarization, and bare ground. There were also three types of sowing: direct, indirect, and pre-germinated. Harvest was performed 81 days after planting and, after the yield evaluation, the following economic indicators were evaluated: costs, revenues, profitability, profit margin, family labor remuneration, and production to cover costs. Considering the costs with inputs and services as of 2018 and the technical coefficients obtained during the experiment, the profit margin was higher than other investments, such as savings accounts. All treatments showed positive profitability, and the B/C ratio was higher than 1,0. Plastic mulching resulted in the highest revenues. The daily wage paid for family labor reached R$ 621.26. Solarization with indirect sowing demanded the highest yield to cover total costs. Regardless of the control method and type of sowing, the profitability is positive and shows a supernormal profit. Plastic mulching allied to direct and pre-germinated sowing increase the revenues.